Co-occurring autism, ADHD, and gender dysphoria in children, adolescents, and young adults with eating disorders: an examination of pre- vs. post-COVID pandemic outbreak trends with real-time electronic health record data - Brown, Tashalee R.; Jansen, Madeline O.; Zhou, A. Ning; Moog, Dominic; Xie, Hui; Liebesny, Katherine V.; Xu, Kevin Y.; Lin, Binx Y.; Deng, Wisteria Y. (Frontiers in Psychiatry, 2024)
BACKGROUND: Incidence rates of autism, attention-deficit/hyperactivity disorder (ADHD), and gender dysphoria (GD) are rising not only in the general population, but particularly among children, adolescents, and young adults with eating disorders (EDs). While ED rates have risen during the COVID pandemic, trends in co-occurring autism, ADHD, and GD have yet to be investigated in detail or at scale by way of large electronic medical record data. OBJECTIVES: To investigate trends in rates of co-occurring autism, ADHD, and GD among children, adolescents, and young adults with EDs in years prior to and during the COVID-19 pandemic. METHODS: We utilized a de-identified multinational electronic health records database (TriNetX) with 48,558 individuals aged 5-26 diagnosed with eating disorders (EDs) at least twice between 2017 and 2022. The primary predictor variable differentiated between the years of each person's index (first) ED diagnosis (2017-2019 vs. 2020-2022). The primary outcome variable was the rate of new co-occurring psychiatric diagnoses of autism, ADHD, and GD in the year following each patient’s first ED diagnosis. We applied propensity score-matched multivariable logistic regressions to compare primary outcomes between 2017-2019 and 2020-2022. RESULTS: Our analysis included 17,445 individuals diagnosed with EDs in 2017-2019 (8% autism, 13.5% ADHD, 1.9% GD) and 31,113 diagnosed with EDs in 2020-2022 (8% autism, 14.6% ADHD, 3.2% GD). After 1:1 propensity score matching, 17,202 individuals from the 2017-2019 cohort were matched to peers mirroring the 2020-2022 cohort. Those diagnosed in 2020-2022 showed a 19% (aOR[95%CI]=1.19[1.07-1.33]), 25% (aOR=1.25[1.04-1.49]), and 36% (aOR=1.36[1.07-1.74]) increase in odds for autism, ADHD, and GD diagnoses, respectively, within the 365 days after the index EDs diagnosis, compared to the 2017-2019 cohort. DISCUSSION: Rates of autism, ADHD, and GD are significantly higher in individuals with ED in the post-pandemic 2020-2022 cohort in comparison to the pre-pandemic 2017-2019 cohort, even after controlling for baseline levels of co-occurring psychiatric diagnoses. Such findings reveal a critical gap in our current understanding of the totality of ways in which COVID-19 may have impacted the onset and clinical course of EDs, autism, ADHD, and GD among children, adolescents, and young adults.